2007
DOI: 10.1128/aem.00576-07
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Haloacid Permease from Burkholderia cepacia MBA4

Abstract: Burkholderia cepacia MBA4 is a bacterium that can utilize 2-haloacids as carbon and energy sources for growth. It has been proposed that dehalogenase-associated permease mediates the uptake of haloacid. In this paper, we report the first cloning and characterization of such a haloacid permease. The structural gene,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 55 publications
1
27
0
Order By: Relevance
“…Although studies of Gordonia sp. KTR9 show that bacteria do not require a dedicated transporter for RDX uptake (13), bacterial genes encoding related functions are frequently situated close to each other (14,34,35). Therefore, we speculated that the aroP-encoded permease might also be involved in the transport of RDX.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies of Gordonia sp. KTR9 show that bacteria do not require a dedicated transporter for RDX uptake (13), bacterial genes encoding related functions are frequently situated close to each other (14,34,35). Therefore, we speculated that the aroP-encoded permease might also be involved in the transport of RDX.…”
Section: Discussionmentioning
confidence: 99%
“…MA1 encodes a putative permease transporter, termed AroP (6), which shares 72% identity with a putative amino acid permease from Mycobacterium vanbaalenii PYR-1 (NCBI accession number YP_952672.1). Two studies have documented permeases located close to genes with related function (14,15). The mode of RDX removal by R. rhodochrous 11Y is unknown, but given the proximity to xplA, it is possible that the aroP-encoded permease is involved in the transport of RDX or its breakdown products.…”
mentioning
confidence: 99%
“…Slow growth was observed for D9 strain compared to Dw possibly due to inefficient substrate uptake system gene in D9 compared to Dw. Yu et al (2007) suggested the uptake of halogenated compound into the bacterial cell was due to haloacid permease. Previous study identified haloalkanoic permease uptake system gene in the dehalogenase producing bacteria was essential for substrate uptake as proposed by Jing et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…The ability for MBA4 to utilize haloacids is conferred by a 2-haloacid dehalogenase Deh4a [1] which has been well characterized [9-11]. A haloacid permease gene, deh4p , which forms an operon with deh4a , was identified by means of chromosome walking [12]. The function of Deh4p was confirmed by heterologous expression in E. coli [13], and its topology determined with a PhoA-LacZ dual reporters system [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of characterizing the MCA-uptake activity of MBA4, it was found that acetate was also recognized by the MCA-inducible uptake system [12,15]. Since acetate and MCA are structurally similar, it is reasonable to speculate that MCA was transported by an acetate-transport system.…”
Section: Introductionmentioning
confidence: 99%